Over a third of childbearing women with HIV would like to breastfeed: A UK survey of women living with HIV. (August 2021) - Nyatsanza, Farai; Gubbin, Jessica; Gubbin, Thomas; Seery, Paula; Farrugia, Pippa; Croucher, Adam; Gilleece, Yvonne; Rosenvinge, Melanie; Roedling, Sherie; Sarner, Liat; Nayagam, Dayawathie; Stradling, Clare; et al.
The World Health Organisation advice for post-partum women living with HIV (WLHs) in low- and middle-income countries is to breastfeed on suppressive antiretroviral treatment and use infant postnatal prophylaxis. In resource-rich settings, where formula feeding is safe, avoidance of breastfeed is advised. A questionnaire was created to survey attitudes to breastfeeding in WLHs in the United Kingdom. This was offered to all eligible pregnant women in the third trimester or within 3 months post-partum who attended HIV outpatient clinics from 2017 to 2018. Ninety-four women completed the questionnaire, 69% were Black African and 92% had an undetectable HIV viral load. Thirty eight percent stated they would like to breastfeed and 89% said they would breastfeed if they were HIV negative. Sixty two percent had community members question why they did not breastfeed, and 66% felt forced to invent a reason why they were not breastfeeding. Current UK guidelines recommend formula feeding, proposing a harm reduction approach to support women with suppressed HIV who wish to breastfeed. Over a third of respondents said they would like to breastfeed because stigma and secrecy remain an issue for WLHs. This suggests that over time more women may choose this option.